Haploidentical donor stem cell transplantation had a lower incidence of bronchiolitis obliterans syndrome compared with HLA-matched sibling donor transplantation in patients with hematologic malignancies: Benefit from ATG? - Weng, Guangyang; Fan, Zhiping; Xue, Huiwen; Huang, Fen; Xu, Na; Jin, Hua; Yu, Sijian; Ye, Zhixin; Fan, Jingchao; Xuan, Li; Liu, Qifa (Frontiers in Immunology, 2022)
Background Haploidentical donor stem cell transplantation (HID-SCT) based on antithymocyte globulin (ATG) for graft-versus-host disease (GVHD) prophylaxis had achieved a similar incidence of chronic graft-versus-host disease (cGVHD) with human leukocyte antigen (HLA)-matched sibling donor stem cell transplantation (MSD-SCT). However, bronchiolitis obliterans syndrome (BOS), which serves as pulmonary cGVHD, was rarely compared between HID and MSD transplantation. Methods One thousand four hundred five patients with hematologic malignancies who underwent allogeneic SCT were enrolled in this retrospective study. Based on donor type, we divided the patients into three groups: HID, MSD, and match unrelated donor (MUD) groups. The cumulative incidences and risk factors of BOS were analyzed. Results The 5-year cumulative incidence of BOS was 7.2% in the whole population. HID transplantation had a lower 5-year cumulative incidence of BOS than MSD transplantation (4.1% vs. 10.0%, p < 0.001) and a similar incidence with MUD transplantation (4.1% vs. 6.2%, p = 0.224). The 5-year cumulative incidence of BOS was lower in the ATG group than that in the non-ATG group in both the whole and MSD populations (4.6% vs. 11.2%, p < 0.001, and 4.1% vs. 11.2%, p = 0.042, respectively). The 5-year incidence of BOS in mixed grafts [peripheral blood stem cell (PBSC) plus bone marrow] group was also lower than that in the PBSC group (4.2% vs. 9.1, p = 0.001). Multivariate analysis showed that HID, ATG, and mixed grafts were protective factors for BOS [odds ratio (OR) 0.3, 95% CI 0.2–0.6, p < 0.001; OR 0.3, 95% CI 0.2–0.7, p = 0.001; OR 0.3, 95% CI 0.1–0.8, p = 0.013], and acute graft-versus-host disease (aGVHD) and cGVHD were independent risk factors for BOS (OR 2.1, 95% 1.1–4.3, p = 0.035; OR 10.1, 95% CI 4.0–25.0, p < 0.001). Conclusions HID transplantation had a lower incidence of BOS than MSD transplantation, which might be associated with ATG and mixed grafts.